2003
DOI: 10.1002/cncr.11374
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the antigens predominantly reacted with serum from patients with hepatocellular carcinoma

Abstract: BACKGROUNDTo identify antigens specifically recognized by the immune surveillance system in patients with hepatocellular carcinoma (HCC), the authors examined two complementary DNA (cDNA) libraries of moderately differentiated HCC by serologic analysis of recombinant cDNA expression libraries (SEREX).METHODSThe libraries were screened with autologous patients' sera, and sequences of the reacted clones were determined. To study the immunoreactivity of the antigens, sera from 20 patients with HCC, from 20 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 88 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…Of these, one is CT antigen (CAGE), which was first reported to be expressed in gastric cancer by Cho et al (2002) and found to be hypomethylated in the majority specimens of human HCC (Cho et al, 2003). Intriguingly, none of the 30 antigens overlapped with the antigens detected by the other two groups (Stenner-Liewen et al, 2000;Uemura et al, 2003), and only one of them (HCA58) was identified in our previous report . Knowledge in the immunogenicity and expression pattern of serologically defined tumour antigens is critical in assessing their relevance to cancer and their therapeutic and diagnostic potentials.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Of these, one is CT antigen (CAGE), which was first reported to be expressed in gastric cancer by Cho et al (2002) and found to be hypomethylated in the majority specimens of human HCC (Cho et al, 2003). Intriguingly, none of the 30 antigens overlapped with the antigens detected by the other two groups (Stenner-Liewen et al, 2000;Uemura et al, 2003), and only one of them (HCA58) was identified in our previous report . Knowledge in the immunogenicity and expression pattern of serologically defined tumour antigens is critical in assessing their relevance to cancer and their therapeutic and diagnostic potentials.…”
Section: Discussionmentioning
confidence: 74%
“…Given that the size of the SEREX-defined cancer immunome, the repertoire of tumour antigens capable of eliciting immune response in cancer patients, is estimated to have 4000 antigens, continued efforts in SEREX screening should extend our understanding of tumour antigens (Lee et al, 2004b). With the aim to identify potent tumour-associated antigens for clinical applications, the SEREX screening of HCC cDNA expression library was performed in several laboratories (Stenner-Liewen et al, 2000;Uemura et al, 2003). These findings imply that different tumourassociated antigens may be identified by SEREX from distinct HCC samples.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP rs660118 maps within the SART1 (squamous cell carcinoma antigen recognized by T cells) gene that is also known as tumor-rejection antigen in brain tumors [28] and in a range of other tumors including hepatocellular carcinoma [29], colorectal cancer [30], renal cell carcinoma [31], and osteosarcoma [32]. Amplification and overexpression of SART1 occurs in head and neck squamous cell carcinoma (HNSCC) [33].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of these proteins reveals that there are many different categories of non-normal proteins recognized by the immune system of a tumor-bearing host. Well-studied tumor antigens include cancer testis (CT) antigens, heat shock proteins, 17 and oncoproteins such as HER-2/Neu and p53. These have been identified as normal cell antigens that are overexpressed in tumor cells 18 .…”
Section: Introductionmentioning
confidence: 99%